2018
DOI: 10.1128/msystems.00024-18
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Evolutionary Conservation of Genes Encoding Multidrug Efflux Pumps in the ESKAPE Pathogens To Identify Antimicrobial Drug Targets

Abstract: Increasing rates of antibiotic-resistant bacterial infection are one of the most pressing contemporary global health concerns. The ESKAPE pathogen group represents the leading cause of these infections, and upregulation of efflux pump expression is a significant mechanism of resistance in these pathogens. This has resulted in substantial interest in the development of efflux pump inhibitors to combat antibiotic-resistant infections; however, no widespread treatments have been developed to date. Our study evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…In this regard, the genus-level analysis and comparison of Enterobacter spp. versus K. pneumoniae indicates high genetic variation (average nucleotide diversity of 0.16 compared to 0.02) (314). This difference suggests that these individual species may have different mechanisms and evolutionary pressures that govern them.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the genus-level analysis and comparison of Enterobacter spp. versus K. pneumoniae indicates high genetic variation (average nucleotide diversity of 0.16 compared to 0.02) (314). This difference suggests that these individual species may have different mechanisms and evolutionary pressures that govern them.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown that genetic diversity of this gene can be captured by three alleles, differing up to 10% at the level of the nucleotide sequence and 5% in the polypeptide sequence; norAI (Yoshida et al, 1990), norAII (also described as norA23 ) (Noguchi et al, 2004) and norAIII (also described as norA1199 ) (Kaatz et al, 1993). The occurrence of norA variants is also strengthened by a recent study by Brooks et al (2018) that refers to the variability of this gene in a set of over 150 S. aureus strains. Although some studies have been conducted to ascertain the impact of this genetic diversity on the efflux activity of NorA (Schmitz et al, 1998; Sierra et al, 2000; Noguchi et al, 2004), this effect remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…Polymyxin E was discovered in the 1940s; yet, later on, it was abandoned in clinical practice due to its increased nephrotoxicity. However, due to the increase of multidrug resistance (MDR) in Gram-negative bacteria, especially in the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species), colistin has been applied in clinical practice for the last few years as the last resort treatment option [2,3]. Currently, colistin resistance is considered a serious problem, due to a lack of alternative antibiotics [4,5].…”
Section: Introductionmentioning
confidence: 99%